Computational study of carrier injection in III-nitride core-shell nanowire-LEDs - Deppner, Marcus; Römer, Friedhard; Witzigmann, Bernd; Ledig, Johannes; Neumann, Richard; Waag, Andreas; Bergbauer, Werner; Strassburg, Martin (IEEE - 2011 Semiconductor Conference Dresden: Technology, Design, Packaging, Simulation and Test, SCD 2011 - International Conference, Workshop and Table-Top Exhibition, 2011)
We report on the computational analysis of a core-shell GaN/InGaN nanowire LED with a capped pyramidal top. The active region consists of a polar multi quantum well (MQW) at the top, a non-polar MQW along the lateral face and a semi-polar one joining them. Differences in the opto-electronic characteristics of the three crystal orientations can be examined, arising from polarization effects as well as the strain-induced bandedge shift. Furthermore the influence of carrier injection efficiency in a nanowire is investigated. © 2011 IEEE.
CRIS-Team Scopus Importer:2021-06-11